(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The rapid integration of AI recommendation systems into e-commerce has changed consumer behavior, especially among Generation Z, who demand a personalized and seamless online shopping experience. This research aims to systematically review how AI-driven personalization influences Gen Z purchasing decisions, with a focus on the balance between personalization, privacy concerns, and brand loyalty. Using systematic literature review methods, this research synthesizes findings from academic journals, exploring emerging trends, ethical considerations, and marketing strategies tailored for Gen Z. The results show that although AI increases engagement through personalization, privacy issues remain an important concern. These findings emphasize the need for e-commerce platforms to adopt transparent data management practices while leveraging AI to build long-term trust and loyalty.